2020
DOI: 10.1002/sce.21595
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of curricular adaptation strategies for implementation at scale

Abstract: This study examines and compares how developers designed two primary science curricula to support teacher adaptation and enable use of innovative materials at scale. The two cases-Literacy Science (a science and literacy curriculum for grades 2-5) and Science as Inquiry (a curriculum focused on matter for grades 3-5)-were selected because the curricula shared many key features, yet the designers undertook the challenge of designing for adaptation in substantially different ways. Data sources for analysis inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…If teachers are provided with the support they need while making adaptations, more successful adaptations could be achieved through mutual collaboration (Dusenbury et al, 2003). Drayton, Bernstein, Schunn and McKenney (2020) found that collaboration with teachers in the adaptation process enabled more effective adaptations through innovative materials developed by designers without harming the core of the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…If teachers are provided with the support they need while making adaptations, more successful adaptations could be achieved through mutual collaboration (Dusenbury et al, 2003). Drayton, Bernstein, Schunn and McKenney (2020) found that collaboration with teachers in the adaptation process enabled more effective adaptations through innovative materials developed by designers without harming the core of the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…oriented around the units. A professional development program is motivated by findings from prior research suggesting that professional development is more effective when it has the following characteristics: a) long duration (far beyond one-off events or workshops), b) connection to teachers' curricular standards and local expectations, c) opportunities to both learn about and try out the curricular materials and strategies, and d) opportunities to discuss and collaborate with teachers of similar classes but different levels of experience and e) adaptability by teachers (Desimone, 2009;Drayton et al, 2020;Horn et al, 2020). Thus, the professional development involves two face-to-face sessions-one (multi-day and residential) at an outdoor education center specializing in phenomenaand place-based education-and ongoing elements that afford opportunities for teachers to give and receive feedback from trying out or using project materials.…”
Section: Plan and Carry Out A Professional Development (Pd) Program F...mentioning
confidence: 99%
“…Posto isso, nos apoiamos nas ideias de Sasseron (2015) de que o ensino por investigação "extravasa o âmbito de uma metodologia de ensino apropriada apenas a certos conteúdos e temas, podendo ser colocada em prática nas mais distintas aulas, sob as mais diversas formas e para os diferentes conteúdos" (p. 58) e consideramos que esta abordagem didática também é adequada para articular conceitos estudados em cursos de ensino superior, uma vez que os elementos a serem investigados são elementos da ciência e não apenas de determinada etapa da educação formal. No ensino superior, os estudantes podem, inclusive, desenvolver raciocínios com elementos mais abstratos e utilizarem ferramentas matemáticas mais avançadas para elaborar conclusões e construir entendimento sobre os conceitos (Ponte, Mata-Pereira, Henriques, 2012) Não há um consenso entre os pesquisadores e educadores sobre as características do ensino por investigação (Teig;Scherer;Kjaernsli, 2020;Drayton et al, 2020;Barcellos et al, 2019;Maeng et al, 2019). Entretanto, perdura a concepção de que esta é uma abordagem que aproxima os estudantes das práticas científicas, abarcando ações manipulativas e intelectuais na resolução de problemas e entendimento de conceitos e fenômenos Souza, 2019).…”
Section: Ensino Por Investigaçãounclassified